Decoherence effect in neutrinos produced in microquasar jets - Mosquera, Mercedes Elisa (2018)
We study the effect of decoherence upon the neutrino spectra produced in microquasar jets. In order to analyse the precession of the polarization vector of neutrinos we have calculated its time evolution by solving the corresponding equations of motion, and by assuming two different scenarios, namely: (i) the mixing between two active neutrinos, and (ii) the mixing between one active and one sterile neutrino. The results of the calculations corresponding to these scenarios show that the onset of decoherence does not depends on the activation of neutrino-neutrino interactions when realistic values of the coupling are used in the calculations. We discuss also the case of neutrinos produced in windy microquasars and compare the results which those obtained with more conventional models of microquasars.